2018
DOI: 10.3389/fpsyg.2018.02039
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Attachment Style in Adulthood, Alexithymia, and Dissociation in Alcohol Use Disorder Inpatients. Mediational Model

Abstract: Background: Attachment theory is a widely used framework for understanding emotion regulation as well as alexithymia, and dissociation and this perspective has also been applied to understand alcohol use disorders. Apart from these theoretical suggestions, there has been scarce empirical research on this subject-matter. Therefore, the objective of the present study was to investigate potential associations between attachment style in adulthood, alexithymia, and dissociation in alcohol use disorder inpatients.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 61 publications
(64 reference statements)
2
10
0
Order By: Relevance
“…These findings are also clinically relevant given that PTSD and alcohol use are highly comorbid and alcohol use among individuals with PTSD has been linked to greater PTSD severity and reduced treatment response (Kilpatrick et al, 2003 ; Pietrzak et al, 2011 ). Moreover, dissociation has also been linked to alcohol use and its related problems (Craparo et al, 2014 ; Evren et al, 2011 ; Zdankiewicz‐Ścigała & Ścigała, 2018 ). Taken together, dissociation plays a unique role in the relation between PTSD severity and alcohol‐related problems making it a critical target for intervention among clinical samples to potentially increase treatment response among individuals with PTSD endorsing alcohol use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are also clinically relevant given that PTSD and alcohol use are highly comorbid and alcohol use among individuals with PTSD has been linked to greater PTSD severity and reduced treatment response (Kilpatrick et al, 2003 ; Pietrzak et al, 2011 ). Moreover, dissociation has also been linked to alcohol use and its related problems (Craparo et al, 2014 ; Evren et al, 2011 ; Zdankiewicz‐Ścigała & Ścigała, 2018 ). Taken together, dissociation plays a unique role in the relation between PTSD severity and alcohol‐related problems making it a critical target for intervention among clinical samples to potentially increase treatment response among individuals with PTSD endorsing alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, dissociation has also been linked to alcohol (Craparo et al, 2014 ; Evren et al, 2011 ; Zdankiewicz‐Ścigała & Ścigała, 2018 ) and/or substance use (Najavits & Walsh, 2012 ; Schäfer et al, 2010 ; Wenzel et al, 1996 ). Prior reports have examined dissociation as a predictor variable with alcohol or substance use and its related problems as outcomes (Craparo et al, 2014 ; Evren et al, 2011 ; Najavits & Walsh, 2012 ; Schäfer et al, 2010 ; Wenzel et al, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the consideration of different emotions and their role in SUD is of great importance, the absence of these emotions or of their perception has to be considered as well: For example, a recent study (153) found that insecure attachment also seems to be associated with dissociation and alexithymia in individuals with SUD. As they inhibit the identification and verbalization of emotions, dissociation and alexithymia also impair the communication with others and thus the mutual understanding (153).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found a link between alexithymic and adult attachment traits (Bekker et al 2007;Berry et al 2007;De Rick and Vanheule 2007;Gong et al 2014;Hexel 2003;Lyvers et al 2017Lyvers et al , 2019Montebarocci et al 2004;Mousavi et al 2016;Taylor et al 2014;Zdankiewicz-Ścigała, Ścigała 2018) indicating that Alexithymia, probably due to its emotional regulation deficits, may solicit forms of insecure adult attachment, characterized by anxiety, fear of rejection and abandonment and difficulties in intimacy in the relationship with the partner. Secure attached adults manage to get in emotional contact with each other, do not fear abandonment and feel the other as a source of security and comfort, while subjects with insecure adult attachment tend to avoid intimacy, to experience anxiety and fear of rejection and abandonment in intimate relationships.…”
Section: Alexithymia Adult Attachment and Self-differentiationmentioning
confidence: 99%